Organizational Process Climate - How Do Employees Perceive It? An Empirical Analysis on An 1SO-9001 Certified Public S - Barman , Arup (Gyan Management Journal, 2009)
Organizational Process. Climate (OPC) is a critical concept, links to continuous improvement; "!Sually discussed and studied within an ambit of total quality oriented organizational development under the business process dimensions. The conceptual basis of the present study is a hit old, but in the context of public sector industry in India, there is dearth of this kind of study. Academic literature with empirical evidence on this aspect is rare. Considering this dearth, the study was conducted in an ISO certified public sector paper industry located in Assam. The main aim of the study is to assess the employees’ perception OPC. The study revealed an ideal OPC no doubt assumes the requirement of employees’ involvement with passion and practices. Employees ’perception toward OPC is highly favorable in this organization.